Cover Image. Issue 12 (16th November 2017) - Ohkubo, H.; Fuyuki, A.; Arimoto, J.; Higurashi, T.; Nonaka, T.; Inoh, Y.; Iida, H.; Inamori, M.; Kaneda, T.; Nakajima, A.
Abstract : The cover image, by H. Ohkubo et al., is based on the Original Article Efficacy of percutaneous endoscopic gastro‐jejunostomy (PEG‐J) decompression therapy for patients with chronic intestinal pseudo‐obstruction (CIPO), DOI:10.1111/nmo.13127 .